SUCCESSFUL SURGICAL TREATMENT FOR RUPTURE OF AN EXTERNAL ILIAC ARTERY PSEUDO ANEURYSM INTO A URETER: A CASE REPORT. - Bhartendu, Kumar; Prasad, Dharmendra; Rahul, Kumar; Sidharth, Nathani; Rajiv, Krishna (Student’s Journal of Health Research Africa, 2024)
Background: Gross hematuria can indicate various urological conditions, including nephrolithiasis, malignancies, infections, and trauma. While most cases are manageable and not life-threatening, certain rare conditions like pseudo-uretero-iliac artery fistula (UIAF) are emergent and potentially fatal, requiring prompt multidisciplinary intervention for diagnosis and treatment. Case: This paper presents a unique case of a ruptured pseudo-iliac aneurysm in the ureter. The patient’s clinical presentation, diagnostic process, and treatment approach, encompassing angiography, cystoscopy, CT imaging, and possibly surgical exploration, are discussed to highlight the complexity and urgency of managing such cases. Conclusion: Pseudo-UIAF represents a critical emergency with varied clinical manifestations from asymptomatic to severe shock. The successful management of this case underscores the importance of a comprehensive diagnostic strategy and a multidisciplinary approach to treatment. Further discussion on the causes, risk factors, and pathophysiology of pseudo-UIAF, along with a review of diagnosis and treatment modalities, enriches our understanding and management of such rare but lethal emergencies.